Flipped Classroom System Based on Guided Inquiry Learning Model Using Discord Application on Reaction Rate - Tuti, Arrum Permata S.; Mawardi, Mawardi; Suryani, Okta (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The 4.0 era has made major changes in educational field. Indonesian also seeks to adapt with 4.0 era by presenting merdeka curriculum that requires learning to be student-oriented while still prioritizing the use of technology in learning. This research develops a learning system by combining a flipped classroom with a guided inquiry model using Discord application as a media that is tested until the validity and practicality stages. The product is considered valid if the Vâ‰¥0.8 result is obtained and very practical if the percentage value of practicality is above 86%. The method used in this research is Educational Design Research (EDR) with the Plomp model. The subjects of this research are 3 chemistry lecturers UNP, 2 teachers and 9 students from SMAN 8 Padang. The data collection instrument in this research was in the form of validity and practicality test questionnaire. Based on the results, the validity value is 0,87 and the practicality value is 90% Â which indicates the system proves to be valid and very practical. This research is expected to be an alternative solution to create chemistry learning in accordance with the demands of the 4.0 era and the kurikulum merdeka, especially on reaction rate.